PRODUKTIVITAS TENAGA KERJA, TITIK IMPAS NILAI PENJUALAN DAN HARGA POKOK PRODUKSI AGROINDUSTRI TEPUNG AREN - Suyudi Suyudi; Nurul Risti Mutiarasari; Zulfikar Noormansyah (Universitas Galuh Ciamis, 2021)
Palm flour is the result of the processing production from the palm tree trunk. This study aims to determine labor productivity, the breakeven point of sales value, the breakeven point of production volume, and the cost of goods manufactured. The research method used is a case study at PT. AKS Gunung Wangi in Kertaharja Village, Cijeungjing District, Ciamis. Quantitative analysis tools used in this research are labor productivity, the break-even point of the sales value and production volume, and the cost of goods manufactured. Labor productivity is measured to determine the economic condition of the labor force of a business carried out, then the break-even point analysis is useful for knowing the relationship between sales value and production volume with prices and other costs, while determining the cost of goods manufactured aims to calculate the cost of using resources. economy in the production process. The results showed that the labor productivity in PT AKS Gunung Wangi's palm flour agroindustry was Rp. 351,562,50 / person working day for one production process. Processing of palm flour in one production process takes 4 days. The breakeven point of the sales value is Rp. 604,118.76 and a production volume of 80.55 kilograms with a production capacity of 1,200 kilograms. The cost of production in the Palm Flour Agroindustry is Rp. 5,167.65 per kilogram.